From Supply Chain to Survival Chain: Strategizing ASEAN-Taiwan Collaboration in the Emerging Indo-Pacific Order - Yang, Alan Hao (AEI Insights, 2023)
Being hit by the Covid-19 pandemic since late 2019, ASEAN countries have been vulnerable in fighting against the pandemic and will be struggling for the post pandemic recovery. In addition, ASEAN countries have also been trapped in the US-China power-politics which has complicated the progress of post-2015 Community consolidation efforts. Implications of the US-China trade friction and strategic competition were re-directing the supply chain in the region and, to some extent, further eroding the ASEAN Centrality. Hence, it is imperative for ASEAN countries to advance further collaboration in strategising ASEAN Centrality and Community building efforts in a more consolidated manner. This paper argues that it is of strategic importance for the ASEAN Community to transform the cooperation for building supply chain to reinvigorating the survival chain (that is, “sc transformation”) for the purpose of securing the interests of ASEAN and move towards the direction of not over-relying on external powers. This article will employ an analytical framework of three Ds (in terms of regional dynamics, development of post-pandemic recovery, and driving forces) for “sc transformation” to address how the transformation from supply chain to survival chain can be achieved. Hence, it begins with outlining the features of regional dynamics of the US-China strategic competition and Covid-19 Pandemic challenges to the ASEAN Community. Then, it will unveil the development of the ASEAN Community in the post-pandemic recovery. Finally, it will address the driving forces of ASEAN Collaboration to strategise its importance in the Indo-Pacific region, including the impetus of Taiwan’s New Southbound Policy.